Soft Law in European community law - Đurđev, Dušanka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Soft law is a term applied to EU measures, such as guidelines, declarations and opinions, which, in contrast to directives, regulations and decisions, are not binding on those to whom they are addressed. However, soft law can produce some legal effects.Special attention in the work is devoted to a problem of a possible role of soft law in wider context of political process development of private law which is discussed within the issue of Lisbon strategy and soft law.The author takes an approach in elaborating on the legal nature and function of soft law